CONCEIVING, DESIGNING AND DEVELOPING TEACHING STRATEGIES IN INSTRUCTIONAL DESIGN - Manolea, Daniela (European Scientific Journal, ESJ, 2013)
This research is a meta-analytic enterprise departing from three premises: a) playing and training should be consistent with the constant deepening of knowing, b) for this purpose, it is necessary to improve instructional design methodologies, c) above all, it requires critical attention to the most effective components of instructional design, teaching strategies. The study is based on a systemic vision oriented to ensure an active and creative learning of knowledge and to rationalize the training process. At the heart of our approach is to clarify the characteristics of teaching strategies and defining operational steps of conceiving, designing and developing teaching strategies